Perclose ProGlide closure devices vs. surgical removal for veno-arterial extracorporeal membrane oxygenation decannulation: a meta-analysis - Zhang, Qian; Guo, Ke; Liu, Yunping; Wei, Wei; Zhao, Kan; Huang, Haijun; Yao, Zuoyi (Frontiers in Cardiovascular Medicine, 2025)
ObjectivePerclose ProGlide closure devices (PPCDs) have become a more commonly used strategy in veno-arterial extracorporeal membrane oxygenation (VA-ECMO) decannulation, but there is still uncertainty regarding their efficacy and safety compared to surgical removal (SR). Therefore, we conducted a meta-analysis to compare the application results of the two methods in VA-ECMO decannulation.MethodsData from PubMed, Cochrane Library, and EMBASE databases were systematically searched through May 2024. Prospective or retrospective studies on the comparison of PPCDs and SR in VA-ECMO decannulation were included. The outcomes included technical success, bleeding events, infections at the decannulation site, vascular complications, overall complications, mortality and duration of hospitalisation.ResultsEight retrospective studies involving 618 patients were included. The results demonstrated that PPCDs significantly reduced infections at the decannulation site and overall complications [odds ratio (OR) = 0.14, 95% confidence interval (CI) 0.05–0.44, P < 0.001], (OR = 0.27, 95% CI 0.16–0.48, P < 0.001). No significant differences were observed in the incidence rates of bleeding events, vascular complications, mortality and duration of hospitalisation between the two groups (P > 0.05). Subgroup analysis revealed that the SR group had a significantly higher risk of the removal site infection compared to the percutaneous pre-closure group (OR = 0.06, 95% CI 0.01–0.29, P = 0.0003).ConclusionPre-closure techniques utilizing PPCDs demonstrate a significant advantage over SR in reducing the overall incidence of complications for VA-ECMO decannulation, particularly in terms of reducing infections at the decannulation site.